Judith S. Kaye in her own words : reflections on life and the law, with selected judicial opinions and articles - Kaye, Judith S., 1938-2016; Greenberg, Henry M., 1961-; Kaye, Luisa M., 1965-; Marcus, Marilyn; Rosenblatt, Albert M. (Albany : State University of New York Press, 2019)
In 1983, Judith S. Kaye (1938-2016) became the first woman appointed to the Court of Appeals, New York's highest court. Ten years later, she became the first woman to be appointed chief judge of the court, and by the time she retired, in 2008, she was the longest-serving chief judge in the court's history. During her long career, she distinguished herself as a lawyer, jurist, reformer, mentor, and colleague, as well as a wife and mother. Bringing together Kaye's own autobiography, completed shortly before her death, as well as selected judicial opinions, articles, and speeches, 'Judith S. Kaye in Her Own Words' makes clear why she left such an enduring mark upon the court, the nation, and all who knew her.
Foreword / Chief Judge Janet DiFiore -- Editorial preface / Honorable Albert M. Rosenblatt -- Biographical introduction / Susan N. Herman -- Milestones -- Reflections on a life in the judiciary, the law, and the world : author's preface -- The New York Court of Appeals -- My arrival on the Court of Appeals -- Getting to work -- The courts dockets and enduring personal lessons -- My transition to chief judge -- The best -- The worst -- ... and everything in between -- The after-life -- Stephen's death -- My route off the court -- My life at Skadden -- From day one to law school -- My years as a lawyer -- One continuous role: as a woman -- Opinions -- Articles and speeches.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 5, 2019).
JSTOR
Keywords: Kaye, Judith S., -- 1938-2016.; New York (State). -- Court of Appeals -- History; Kaye, Judith S., -- 1938-2016; New York (State). -- Court of Appeals; Judges -- New York (State) -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Judges; New York (State); Autobiography; Biography; autobiographies (literary works); decisions (judicial records); Autobiographies; Biographies; Court decisions and opinions; History; Autobiographies; Court decisions and opinions; Biographies; Autobiographies; Recueils de jurisprudence et d'opinions.; Biographies